2015
DOI: 10.1007/s11465-015-0331-4
|View full text |Cite
|
Sign up to set email alerts
|

Dynamic modeling of hydrostatic guideway considering compressibility and inertia effect

Abstract: Hydrostatic guideways are used as an alternative to contact bearings due to high stiffness and high damping in heavy machine tools. To improve the dynamic characteristic of bearing structure, the dynamic modeling of the hydrostatic guidway should be accurately known. This paper presents a "mass-spring-Maxwell" model considering the effects of inertia, squeeze, compressibility and static bearing. To determine the dynamic model coefficients, numerical simulation of different cases between displacement and dynami… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 7 publications
(3 citation statements)
references
References 16 publications
0
3
0
Order By: Relevance
“…Y Du et al 77 introduced compressible fluid in the simulation of rectangular oil pad and established the dynamic model of a hydrostatic guideway, while JS Oh et al 78 used mixed two-probe method (MTPM) to measure the moving error of a hydrostatic guideway. Moreover, Z Wang et al, 79 based on the dynamic model of hydrostatic guideway shown in Figure 30, analyzed the relationship between oil supplying condition and moving error.…”
Section: Rectangular Oil Padmentioning
confidence: 99%
“…Y Du et al 77 introduced compressible fluid in the simulation of rectangular oil pad and established the dynamic model of a hydrostatic guideway, while JS Oh et al 78 used mixed two-probe method (MTPM) to measure the moving error of a hydrostatic guideway. Moreover, Z Wang et al, 79 based on the dynamic model of hydrostatic guideway shown in Figure 30, analyzed the relationship between oil supplying condition and moving error.…”
Section: Rectangular Oil Padmentioning
confidence: 99%
“…The coupling effect between the fluid film and deformation of the shaft was analyzed. Du et al [23] presented a mass-spring-Maxwell model considering the effects of inertia, squeeze and compressibility for the oil film of hydrostatic bearings. Identification results show that mass-spring-Maxwell model is the most appropriate dynamic model for the oil film.…”
Section: Introductionmentioning
confidence: 99%
“…Morosi and Santos (2011) developed a model of the hybrid journal bearing based on the modified general form of the Reynolds equation. Du et al (2015) considered the effects of inertia, squeeze and compressibility to establish a dynamic model of the hydrostatic guideway. The results showed that "mass-spring-damper" model was the most appropriate dynamic model of the hydrostatic guideway.…”
Section: Introductionmentioning
confidence: 99%